A conceptual design of an alternative method for cutting off standby power consumption for office equipment - Tan, Kheng Wee (2012)
Ever since the completion of Politeknik Kuching Sarawak (PKS) first major networking project in 2002, its energy consumption has been in the steady rise. Although the increment was understandable, the increasing energy wastage in terms of standby power consumption by ICT equipment and equipment not being switch off was intolerable. With the aim of finding the solution to this issue, the project was divided into three parts. The first part of the project surveyed the level of awareness among the staff during a monthly assembly and found out despite the high level of awareness among the academic staff, some 38% of them admitted they do not switch off their computer and thus jeopardizing the management’s desire to put a stop to energy wastage. Secondly, the field measurement of ten types of selected office equipment has been carried out with minimum five samples of measurement taken whenever possible to produce a good average value. The bottom-up estimation method then put the annual standby power consumption of PKS at 64,653.11 kWh and cost a staggering RM 21,982.06. Finally, unlike the conventional method of using current level detection to detect appliances going into standby mode, the project came out with an alternative standby power cut-off system that utilises light source as a mean of controlling the system and is suitable for the usage in an office environment.